COURT REPORTING; MAKING INDIAN JUDICIAL SYSTEM FAIR - Sunil Kumar Sharma, Amit Sharma (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Mass media is considered as a guard dog for the Judiciary and other pillars of democracy. Mass media support in the fair trial of court proceeding and give proper atmosphere in the deliverance of justice to all. The present study is descriptive in nature and deals with the survey method. The data is collected with the help of a questionnaire form the journalist and lawyers. The result indicates that almost half of the respondent believes that the media helps to make a case strong and can influence public opinion as well as a judicial opinion.